2017
DOI: 10.4172/2329-9126.1000333
|View full text |Cite
|
Sign up to set email alerts
|

Paraumbilical Perforator Flap: A Good Choice for the Repair of the Deep Soft Tissue Defects in the Hand and Forearm

Abstract: Objective: Severe trauma to the hand or forearm often results in the deep soft tissue defect with the exposure of tendon or bone, which needs to be repaired by skin flaps. In this study, we introduced the use of paraumbilical perforator flap in the repair of such defects, and discussed its advantages and disadvantages.Methods: From Jan. 2006 to Dec. 2016, 14 patients with deep soft tissue defects in the hand and forearm were admitted into our clinic. The defects were caused by hot-crush injury (n=2), electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…11 Jim Wang et al in a series of 14 patients reported a flap of mean dimensions of 6 cm to 8 cm in width and 16 cm to 20 cm in length. 12 In a series of 12 patients, flap dimensions ranging from 6 cm to a maximum length of about 18 cm were used. 13 Most of his flaps extended up to the anterior axillary line, with only five extending to the mid axillary line.…”
Section: Discussionmentioning
confidence: 99%
“…11 Jim Wang et al in a series of 14 patients reported a flap of mean dimensions of 6 cm to 8 cm in width and 16 cm to 20 cm in length. 12 In a series of 12 patients, flap dimensions ranging from 6 cm to a maximum length of about 18 cm were used. 13 Most of his flaps extended up to the anterior axillary line, with only five extending to the mid axillary line.…”
Section: Discussionmentioning
confidence: 99%
“…11 Jim Wang et al in a series of 14 patients reported a flap of mean dimensions of 6 cm to 8 cm in width and 16 cm to 20 cm in length. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Một số tác giả gọi các nhánh xuyên này là nhánh xuyên hàng trong và hàng ngoài. Ngoài ra, một số tác giả gọi những nhánh xuyên chui qua cân ở thẳng bụng ở gần rốn và cung cấp máu cho mô dưới da liền kề là nhánh xuyên cạnh rốn hoặc nhánh xuyên cạnh đường giữa hay nhánh xuyên cạnh cơ [1], [6], [7]. Chính vì tính phong phú của nhánh xuyên động mạch thượng vị dưới sâu nên có thể dễ dàng lựa chọn một nhánh xuyên để thiết kế vạt chỉ bằng cách sử dụng siêu âm Doppler cầm tay để dò tín hiệu mạch máu.…”
Section: Tăng Tính Linh Hoạt Trong Thiết Kế Và Sử Dụng Vạtunclassified
“…Để bảo đảm vạt sẽ sống tốt sau cắt cuống, chỉ được cắt cuống vạt sau khi kẹp cuống mà tình trạng cấp máu cho vạt vẫn bảo đảm tốt (vạt không bị thiếu máu tái nhợt hay ứ máu gây xung huyết), có thể cắt cuống vạt sau 24 giờ sau khi kiểm tra sự cấp máu từ nền ghép cho kết quả tốt [4], [6].…”
Section: Giảm Thời Gian đIều Trị Bằng Cách Kẹp Cuống Vạt Sớmunclassified